Non-Shariah Compliance Risks (NCR) and the Danger of Potential Fraud in the Islamic Financial Institutions: A Conceptual Framework - Norzitah Abdul Karim; Amirul Afif Muhamat; Mohamad Nizam Jaafar; Munira Abu Bakar; Salina Kassim (Information Management and Business Review, 2024)
This research paper is a conceptual study that aims to examine financial fraud and its relation to non-compliance to Shariah for the Islamic financial institution in Malaysia. The study is unique because it seeks to understand how deviations from Shariah guidelines could contribute to financial misconduct, examining the specific non-Shariah compliance risks that arise when the deviation of internal control fails to align with Islamic law. Utilizing quantitative methodology, this study adopts and adapts from an existing structured questionnaire survey to collect data. This study also employs Structural Equation Modelling (SEM) in its analysis of the data. The implication of this study for policymakers includes the development of an effective strategy for mitigating financial fraud and ensuring Shariah compliance, thus ensuring the integrity and reputation of the Islamic financial sectors. This will undoubtedly contribute to the stability of the economy.